Rational Expressions: (lesson 3 of 3)
Adding and Subtracting Rational Expressions
Rational Expressions with the Same Denominator
To add/subtract rational expressions with the same denominator
1. Add/subtract the numerators. Write this sum/difference as the numerator over the common denominator.
2. Reduce to lowest terms.
Example 1
Simplify the following:
5y4x+5y6x
Solution
These fractions already have a common denominator
1: Write this sum as the numerator over the common denominator:
5y4x+5y6x=5y4x+6x
2: Reduce to lowest terms:
5y4x+5y6x=5y4x+6x=5y10x=y2x
Example 2
Simplify the following:
x+44x−1−x+42x−9
Solution
Again, these already have a common denominator
1: Write this sum as the numerator over the common denominator:
x+44x−1−x+42x−9=x+4(4x−1)−(2x−9)
2: Reduce to lowest terms:
x+44x−1−x+42x−9=x+4(4x−1)−(2x−9)=
=x+44x−1−2x+9=
=x+42x+8=
=x+42(x+4)=2
Exercise 1: Simplify the following expression
Adding or Subtracting Rational Expressions with Different Denominators
1. Factor each denominator completely.
2. Build the LCD of the denominators.
3. Rewrite each rational expression with the LCD as the denominator.
4. Add/subtract the numerators.
Example 3:
Simplify the following:
x2−3x+25x−1+2x−43
Solution 3:
1: Factor each denominator completely.
x2−3x+25x−1+2x−42=(x−1)(x−2)5x−1+2(x−2)3
2: Build the LCD of the denominators.
LCD=2(x−1)(x−2)
3: Rewrite each rational expression with the LCD as the denominator.
x2−3x+25x−1+2x−43=(x−1)(x−2)5x−1+2(x−2)3=
=2(x−1)(x−2)2(5x−1)+2(x−1)(x−2)3(x−1)
4: Add the numerators.
x2−3x+25x−1+2x−43=(x−1)(x−2)5x−1+2(x−2)3=
=2(x−1)(x−2)2(5x−1)+2(x−1)(x−2)3(x−1)=
=2(x−1)(x−2)2(5x−1)+3(x−1)=
=2(x−1)(x−2)13x−5
Example 4:
Simplify the following:
x2−2x−35x+1−x2−x−65x−3
Solution 4:
1: Factor each denominator completely.
x2−2x−35x+1−x2−x−65x−3=(x−3)(x+1)5x+1−(x−3)(x+2)5x−3
2: Build the LCD of the denominators.
LCD=(x−3)(x+1)(x+2)
3: Rewrite each rational expression with the LCD as the denominator.
x2−2x−35x+1−x2−x−65x−3=(x−3)(x+1)5x+1−(x−3)(x+2)5x−3=
=(x−3)(x+1)(x+2)(5x+1)(x+2)−(x−3)(x+1)(x+2)(5x−3)(x+1)
4: Subtract the numerators.
x2−2x−35x+1−x2−x−65x−3=(x−3)(x+1)5x+1−(x−3)(x+2)5x−3=
=(x−3)(x+1)(x+2)(5x+1)(x+2)−(x−3)(x+1)(x+2)(5x−3)(x+1)=
=(x−3)(x+1)(x+2)(5x+1)(x+2)−(5x−3)(x+1)=
=(x−3)(x+1)(x+2)(5x2+10x+x+2)−(5x2+5x−3x−3)=
=(x−3)(x+1)(x+2)5x2+10x+x+2−5x2−5x+3x+3)=
=(x−3)(x+1)(x+2)9x+5
Exercise 2: Simplify the following expression